2022
DOI: 10.3390/microorganisms10101998
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Profiling Analysis of Phosphate-Solubilizing Mechanism of Pseudomonas Strain W134

Abstract: Phosphate-solubilizing bacteria (PSB) can alleviate available phosphorus deficiency without causing environmental pollution, unlike chemical phosphate fertilizers. However, the phosphate solubilization mechanisms of PSB are still unclear. Transcriptome sequencing was used to analyze the expression patterns of differential expressed genes (DEGs) of the phosphate-solubilizing bacterium W134 under the conditions of soluble phosphorus (group A), insoluble phosphorus (group B), and lacking phosphorus (group C). Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Phosphorus-solubilizing bacteria can transform insoluble phosphorus, which is difficult for plants to absorb and utilize, into effective forms and improve the utilization efficiency of soil phosphorus (Kalayu, 2019 ). Pseudomonas is agricultural soil's main phosphorus-solubilizing bacteria (PSB) (Wang et al, 2022 ). Soil AP content was closely related to soil bacterial community and wheat yield, indicating that soil phosphorus was an important factor driving soil microbial community and wheat yield changes (Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus-solubilizing bacteria can transform insoluble phosphorus, which is difficult for plants to absorb and utilize, into effective forms and improve the utilization efficiency of soil phosphorus (Kalayu, 2019 ). Pseudomonas is agricultural soil's main phosphorus-solubilizing bacteria (PSB) (Wang et al, 2022 ). Soil AP content was closely related to soil bacterial community and wheat yield, indicating that soil phosphorus was an important factor driving soil microbial community and wheat yield changes (Chen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…4, the increasing content of acetic acid indicated that the activity of TCA cycle was limited under NH 4 + stress. Recent studies have shown that different P sources in uenced the types of organic acids [51]. Arvind et al found that the generation of formic acid was limited to the dissolution of TCP, and oxalic acid production to the solubilization of MRP, URP and NCRP [52].…”
Section: Discussionmentioning
confidence: 99%
“…The production of succinic acid was related to PS activity of Bacillus megaterium , while oxalic acid and citric acid were the main organic acids released by Pseudomonas sp [ 3 ]. The secretion of organic acids was also influenced by the types and concentrations of P sources [ 47 ]. Arvind et al found that the generation of formic acid was limited to the dissolution of TCP, and oxalic acid production to the solubilization of Mussoorie rock phosphate, Udaipur rock phosphate, and North Carolina rock phosphate [ 48 ].…”
Section: Discussionmentioning
confidence: 99%